Layer 1 NDNF interneurons form distinct subpopulations with opposite activation patterns during sleep in freely behaving mice - Aurélie Brécier; Gaëlle Mailhos; Przemyslaw Jarzebowski; Yuqi Li; Ole Paulsen; Y. Audrey Hay (Proceedings of the National Academy of Sciences, 2025)
Non–rapid eye movement (NREM) sleep facilitates memory consolidation by transferring information from the hippocampus to the neocortex. This transfer is thought to occur primarily when hippocampal sharp-wave ripples (SWRs) and thalamocortical spindles are synchronized. However, the mechanisms underlying this synchronization remain unknown. In this study, we investigated the role of cortical layer 1 neuron-derived neurotrophic factor (NDNF)-expressing (L1 NDNF) interneurons in gating information transfer during SWR-spindle synchronization in NREM sleep. Using simultaneous cell-type specific calcium imaging with a head-mounted microscope and local field potential recordings in freely moving mice, we compared the activity of L1 NDNF and L2/3 neurons across vigilance states and during NREM-specific oscillations. Our findings reveal that L1 NDNF neurons form three distinct populations, assembling into cell networks tuned to specific sleep stages. REM active L1 NDNF and L2/3 neurons exhibit opposite activation patterns during spindles. While L2/3 cells are mostly inactive during SWR, NREM and REM active L1 NDNF cells inhibit the network upon SWR onset depending on their coupling with spindles. L1 NDNF neurons mediate slow inhibition primarily via GABA B receptors. Systemic application of a GABA B receptor antagonist resulted in decreased neuronal coupling of pyramidal cells but did not change the responses during SWRs. Overall, these findings highlight the potential role of L1 NDNF neuron-mediated inhibition in the response to synchronized sleep oscillations, with possible implications for memory consolidation.